Spray drying conditions for protein hydrolysate of crocodile meat - Cang, M. H. (2024)
The objective of this study is to screen the effects of several parameters (i.e., drying aid concentration, inlet air temperatures, and feed flow rates) on the spray drying process of crocodile meat protein hydrolysate. The results showed that the experimental parameters exhibited significant effects on recovery of dry matter, recovery of proteins and the obtained powder properties (total protein content, moisture content and antioxidant capacity). Besides, inlet air temperature and drying aid concentration also significantly impacted response variables. The conditions for maximum recovery of dry matter, maximum recovery of proteins, and minimum moisture content of the spray-dried powder were found at maltodextrin concentration of 19.47% (w/w), inlet air temperature of 142.71oC, and input feed flow rate of 10 mL/min. These conditions correspond to the recovery of dry matter of 69.51%, protein recovery yield of 76.94%, powder humidity of 5.33%, and powder antioxidant activity of 1.87 mg/mL.